2018
DOI: 10.1007/s10995-018-2584-0
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Breastfeeding Among Hispanic American Women: A Systematic Review

Abstract: Introduction Hispanic immigrants are more likely to breastfeed than are Hispanics born in the US, in part due to their acculturation. This paper aims to systematically review the existing literature on the association between acculturation and Hispanics' breastfeeding behaviors. Methods The systematic search used major databases such as Medline and PubMed, and it followed the PRISMA checklist. The scientific quality of the studies was rated using the Quality Assessment Tool for Quantitative Studies. Results We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 28 publications
3
18
1
Order By: Relevance
“…The finding that African-American women and U.S.-born Hispanic women tend to have the worst outcomes is consistent throughout the literature [18],[19]. Research has document that high-acculturated Hispanic women are less likely to intend to or breastfeed their newborn, compared with low-acculturated Hispanic women [23]. One possible explanation for this is that African-American, U.S.-born Hispanic, and immigrant Hispanic women tend to share low-income status; however, immigrant Hispanic women also tend to stay at home instead of joining the labor force, which makes it easier to have time to breastfeed.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The finding that African-American women and U.S.-born Hispanic women tend to have the worst outcomes is consistent throughout the literature [18],[19]. Research has document that high-acculturated Hispanic women are less likely to intend to or breastfeed their newborn, compared with low-acculturated Hispanic women [23]. One possible explanation for this is that African-American, U.S.-born Hispanic, and immigrant Hispanic women tend to share low-income status; however, immigrant Hispanic women also tend to stay at home instead of joining the labor force, which makes it easier to have time to breastfeed.…”
Section: Discussionsupporting
confidence: 75%
“…Alternatively, Wouk et al [22] suggest Hispanic women tend to have low rates of breastfeeding, but did not examine differences among subgroups. Some studies have demonstrated that examining this relationship by subgroups of Hispanic populations is important because certain groups have different behaviors based on immigrant status or country of origin [16],[23].…”
Section: Introductionmentioning
confidence: 99%
“…In our experience the rate of women with PGDM who intended to BF ranges from 66 to 79% [11,26]. Like others, we noted that intention to BF and prior BF experience are strong predictors of exclusive or partial BF at discharge from the hospital [8,11,26,27,[42][43][44][45]. Unfortunately, the rate of women healthy or otherwise who do not intend to BF remained consistent [11,16,26,27].…”
Section: Interpregnancy Intervals Intention To Bf and Infant Feedingsupporting
confidence: 49%
“…Immigrant Hispanic and black women were more likely to report breastfeeding cessation because the infant lost interest. Nonnative populations tend to have higher breastfeeding initiation and duration rates, as immigrant women may come from countries where breastfeeding is the norm. Previous work has suggested that women's country of education, more so than country of origin, may be an important determinant of breastfeeding discontinuation among Latina women .…”
Section: Discussionmentioning
confidence: 99%